The Chariot Festival of Karunamaya Lokeswor - Bajracharya, Nirmal Siddhi (Journal of International Buddhist Studies, 2016)
Nepal Mandala – the ancient name of Kathmandu Valley is indeed a cradle of civilization that has continued for centuries making it the center for cultural and religious evolution of Nepal. Nepal Mandala the valley of Kathmandu was said to be a great lake which was drained by Manjushree by cutting a hill on the southern part of the lake to form the inhabitable valley. The earliest inhabitants of the valley were the “Nears” and through centuries the development of the Newar civilization created the most architecturally endowed city- the Nepal Mandala. The original Newars were Buddhists though Hinduism also developed with the migration and settlement of various other ethnic groups. The original Buddhist religion and traditions of the Newars were slowly infiltrated by Hindu culture depending on the strength of the ruling clans controlling the city nation. However, history has been a witness to a peaceful coexistence of Buddhism and Hinduism among the people of this valley further enriching the social, traditional, religious and ritualistic diversity of the city. Kathmandu Valley is truly a city of gods with temples, stupas, and statues in every corner of the city. There is never a month that one or the other kind of religious ceremony is celebrated by the people in the valley. The life style of the people is definitely a living culture and tradition that has helped to conserve the religion and tradition of Buddhism. Any researcher or anthropologist researching on Nepal cannot complete his studies without studying the ‘Newar’ people and their culture.